Imbibing Values through Science Education - Nambiar, Seema R. (Voices of Teachers and Teacher Educators, 2020)
The purpose of education is to nurture and guide the child for life. The author here is focusing on creating learning experiences for integrating cognitive- affective pedagogy in the classroom for the holistic development of the child. This paper emphasizes the need for an integrated approach of inculcating skills and values through concept analogues, classroom activities and experiments. This will help the teacher and the teacher educators in relating the content areas/ activities with the skills and values and implementing the same during the teaching learning process in the classroom. Value inculcation through Science teaching will help the learner to think independently, to reflect and to critically evaluate their own thoughts which in turn will reflect in their behaviour. Moreover, this will enable students to achieve both academic and human excellence to create a vision for a sustainable global society.